Vice-Chancellor receives AGBA award - UMP, PNC
Universiti Malaysia Pahang (UMP) Vice-Chancellor, Professor Dato’ Dr. Daing Nasir Ibrahim received AGBA Life-Time Achievement Award 2010 in conjunction with the 7th Academy for Global Business Advancement (AGBA) World Congress organised by Academy for Global Business Advancement (AGBA), USA and Universiti Putra Malaysia’s School of Graduates Studies at Palm Garden Hotel Putrajaya during the gathering held on December 1-3, 2010.